2018
DOI: 10.1002/ece3.4186
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of ontogenetic movement in maintaining population structure in fish using otolith microchemistry

Abstract: Identifying the mechanisms maintaining population structure in marine fish species with more than a single dispersing life stage is challenging because of the difficulty in tracking all life stages. Here, a two‐stage otolith microchemistry approach to examining life‐stage movement was adopted, tracking a year‐class from the juvenile to adult stage and inferring larval sources from clustering, in order to consider the mechanisms maintaining population structuring in North Sea cod. Clustering of near‐core chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 68 publications
1
26
0
1
Order By: Relevance
“…Therefore, for this stock, the management challenges refer principally to an increase in stock size post‐collapse and the resulting area expansion. The current displacement of North Sea cod spawning grounds to the north‐east North Sea (Sundby et al, 2017; Wright et al., 2018) is certainly attributed to climate change but accelerated by a parallel overfishing in the central‐western North Sea (Engelhard et al, 2014). The overall stock situation is still poor (ICES, 2020) (Figure 3), although seeing recent positive trends locally in the proportion of larger cod greater than 40 cm corresponding with reductions in EU's bottom trawl efforts (Engelhard, Lynam, Garcia‐Carreras, Dolder, & Mackinson, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, for this stock, the management challenges refer principally to an increase in stock size post‐collapse and the resulting area expansion. The current displacement of North Sea cod spawning grounds to the north‐east North Sea (Sundby et al, 2017; Wright et al., 2018) is certainly attributed to climate change but accelerated by a parallel overfishing in the central‐western North Sea (Engelhard et al, 2014). The overall stock situation is still poor (ICES, 2020) (Figure 3), although seeing recent positive trends locally in the proportion of larger cod greater than 40 cm corresponding with reductions in EU's bottom trawl efforts (Engelhard, Lynam, Garcia‐Carreras, Dolder, & Mackinson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It should, however, be emphasized that it may be difficult to quantitatively assess the separate effects of climate and fishing, as demonstrated in these waters by Engelhard, Righton, and Pinnegar (2014). The major spawning areas are now found at the shelf near the western slope of the Norwegian Trench and in the northernmost part of the North Sea in the waters off Scotland and Shetland (Sundby et al, 2017; Wright et al., 2018). This cod spawning ground displacement might also be an indirect effect of higher temperatures; the main abundance of Calanus finmarchicus (Calanidae), the key prey for the cod larvae (Beaugrand, Brander, Lindley, Souissi, & Reid, 2003), now appear in the same region of the North Sea (Sundby, 2000).…”
Section: Case‐studies Illustrating How Climate May Impact Stock Distrmentioning
confidence: 99%
“…Natal sources of age-1 fish RF clustering analysis of the near-core trace element data was performed in age-1 fish to determine the number of larval sources contributing to the sample. This approach proved to be useful for natal origin-related investigations when there is no previous baseline of potential larval sources (Gibb et al 2017;Régnier et al 2017;Wright et al 2018). Moreover, the RF clustering approach does not require continuous multivariate data with normal distribution (Shi and Horvath 2006), an assumption that is often violated when working with otolith microchemistry data.…”
Section: Comparison Of Classification Methodsmentioning
confidence: 99%
“…In the North Sea (International Council for the Exploration of the Sea (ICES) 4) and off the Scottish west coast (ICES 6a), studies of single nucleotide polymorphic (SNP) markers of spawning cod provide evidence of barriers to gene flow between the deeper north east North Sea region between 100 -200 m and the shallower shelf region throughout these two stock areas, except for the Clyde Sea (Heath et al, 2014). Analyses of otolith chemistry, comparing larval, juvenile and adult parts for the same year-class in the North Sea, suggests that this reproductive isolation is maintained by a combination of hydrographical isolation of early life-stages and either fidelity or natal homing of later stages (Wright et al, 2006a;Neat et al, 2014;Wright et al, 2018). Spatio-temporal differences in maturity at size seem to be consistent with the scale of mixing suggested by tagging (Wright et al, 2006a;Neat et al, 2014), with differences found among cod in the north west, north east and southern North Sea and Scottish west coast (Yoneda & Wright, 2004;Wright et al, 2011).…”
Section: Introductionmentioning
confidence: 99%